ISLAMIDAR SEBAGAI TOKOH MUSIKTRADISIONAL MINANGKABAU: GAGASAN, KREATIVITAS, DAN KONTRIBUSINYA - Tiffani Manda Sari; Ardipal Ardipal; Syahrel Syahrel (SENDRATASIK UNP, 2014)
Abstract This a article was intended to reveal the phenomena of Islamidar in the traditional music art in West Sumatera including him ideas, creativity and him contribution toward the development of Minagkabau traditional music in West Sumatera. This was a qualitative research which used Biography method. The data was gotten through interview, direct observation and documentation. The instruments of the research were the researcher herself, note-book, recorder and audio visual media. The data gathered then was analyzed by using ethnography data analysis technique. The research findings revealed that Islamidar had a talent in music since he was a child. He learned music in the age of 5, and when he was 16, he had become a great Talempong player. He had arranged a practical scale of Talempong to accompany a song or a dance. With him creativity, Islamidar had created more popular technique of playing Talempong, music for accompanying dance and arrangement of Talempong beats. Furthermore, Islamidar had a contribution in popularizing Talempong musical instruments so that there was an increasing interest among the society and artists either in or out of country. At last, the composition of Talempong had become a Talempong orchestra recently. Kata Kunci: Islamidar, Musik Talempong, dan Tangga Nada Talempong